2018
DOI: 10.1016/j.jinorgbio.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and DNA interactions of [Pt3(TPymT)Cl3], the trinuclear platinum(II) complex of the TPymT ligand

Abstract: The triplatinum complex of the 2,4,6-Tris(2-pyrimidyl)-1,3,5-triazine ligand, PtTPymT hereafter, has been prepared and characterized for the first time. NMR studies point out that the three platinum(II) centers possess an identical coordination environment. The interactions of PtTPymT with DNA were explored in comparison to the free ligand. Specifically, fluorescence, mass spectrometry, viscometry and melting measurements were carried out. In contrast to expectations, the obtained data reveal that no intercala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Ultrapure water (Sartorius) was the reaction medium together with a NaCl 0.1 M + NaCac (sodium cacodylate) aqueous buffer used to maintain pH 7.0. In EB/DNA exchange experiments, DNA was saturated with EB according to a known procedure; in brief, EB was added to DNA until the fluorescence emission increase at the excitation/emission wavelength selective for the EB/DNA intercalated complex faded out ( T = 25.0 °C, C DNA = 1.30 × 10 –4 M, C EB = 5.33 × 10 –5 M, C DNA / C EB = 2.4, λ ex = 520 nm, λ em = 595 nm). Subsequently, increasing amounts of the stock metal complex solution were added to the EB/DNA mixture (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Ultrapure water (Sartorius) was the reaction medium together with a NaCl 0.1 M + NaCac (sodium cacodylate) aqueous buffer used to maintain pH 7.0. In EB/DNA exchange experiments, DNA was saturated with EB according to a known procedure; in brief, EB was added to DNA until the fluorescence emission increase at the excitation/emission wavelength selective for the EB/DNA intercalated complex faded out ( T = 25.0 °C, C DNA = 1.30 × 10 –4 M, C EB = 5.33 × 10 –5 M, C DNA / C EB = 2.4, λ ex = 520 nm, λ em = 595 nm). Subsequently, increasing amounts of the stock metal complex solution were added to the EB/DNA mixture (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence measurements were performed on a PerkinElmer LS55 instrument (temperature ±0.1 °C). In EtBr/DNA exchange experiments, DNA was saturated with EtBr according to a documented procedure: 46 i.e., until the end of the fluorescence emission increase at the excitation/emission wavelength selective for the EtBr/DNA intercalated complex (λ ex = 520 nm, λ em = 595 nm). Subsequently, increasing amounts of 2b stock solution were added to the EtBr/DNA mixture.…”
Section: Synthesis Of [Fementioning
confidence: 99%
“…and the [(TPymT)Pt 3 (Cl) 3 ](OH) 3 complex toward interaction with DNA was carried out via viscometry, mass spectrometry, melting, and fluorescence measurements. The results showed that there is no intercalative binding between the DNA and [(TPymT)Pt 3 (Cl) 3 ](OH) 3 complex 195 [149] [150] The hydrolysis of TPymT in presence of copper sulfate or perchlorate into the corresponding bis (2-pyrimidylcarbonyl)amidate (bpcam) were reported by de Castro Gomes et al in 2005. The copper complexes were separated either as mononuclear or dinuclear complexes in a distorted square pyramidal coordination geometry (Scheme 74).…”
Section: Safin Et Al Reported the Coordination Chemistry Of Lead Nitrate Withmentioning
confidence: 84%
“…and the [(TPymT)Pt 3 (Cl) 3 ](OH) 3 complex toward interaction with DNA was carried out via viscometry, mass spectrometry, melting, and fluorescence measurements. The results showed that there is no intercalative binding between the DNA and [(TPymT)Pt 3 (Cl) 3 ](OH) 3 complex 195 [149] (Scheme 72).…”
Section: Safin Et Al Reported the Coordination Chemistry Of Lead Nitrate Withmentioning
confidence: 99%